Criminal Acts of Physical and Non-Physical Sexual Violence in University - Nur Azisa; Nur Amelinda Kharia; Maskun; Nurul Hidayat Ab Rahman; Arnita Pratiwi Arifin (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
Sexual violence in educational environments, especially universities, is a significant social issue that needs urgent attention. This study highlights the issue of sexual violence in university settings, focusing on understanding the role of victims in cases of sexual violence from a victimological perspective. The purpose of this research is to analyze the extent to which internal and external factors influence victims' decisions to report or not report incidents, as well as to explore victims' involvement in incidents of sexual violence. Using an empirical legal method with a case-based approach, this study combines surveys, interviews, and literature reviews to gather primary and secondary data. The novelty of this research lies in its in-depth analysis of the psychological and social dynamics affecting victims' involvement in sexual violence cases on campus. The findings indicate that in some cases, victims may indirectly contribute to the occurrence of sexual violence due to unawareness of their social surroundings, referred to as "imprudent victims" in victimology. This study recommends establishing a PPKS Task Force and introducing “Sahabat PPKS” in each faculty as strategic measures to create a safe and supportive campus environment for victims. The research aims to contribute to the development of comprehensive protection policies, including legal, psychological, and social support for victims within academic settings.